2020
DOI: 10.1063/5.0018557
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic defects as single-photon emitters in atomically thin MoS2

Abstract: Precisely positioned and scalable single-photon emitters (SPEs) are highly desirable for applications in quantum technology. This Perspective discusses single-photon-emitting atomistic defects in monolayers of MoS2 that can be generated by focused He-ion irradiation with few nanometers positioning accuracy. We present the optical properties of the emitters and the possibilities to implement them into photonic and optoelectronic devices. We showcase the advantages of the presented emitters with respect to atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 69 publications
2
73
0
Order By: Relevance
“…Vacancies introduce a deep center with sharp optical emission, markedly different from previously observed broad luminescence bands [4][5][6][7][8] . Comparing annealed vs. He-ion treated MoS 2 , we establish that the recently discovered single-photon emitters in He-ion irradiated MoS 2 originate from chalcogen vacancies 3 . The latter can be deterministically created with a precision below 10 nm 9 , underscoring the potential of defect engineering for twodimensional (quantum-) optoelectronics.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Vacancies introduce a deep center with sharp optical emission, markedly different from previously observed broad luminescence bands [4][5][6][7][8] . Comparing annealed vs. He-ion treated MoS 2 , we establish that the recently discovered single-photon emitters in He-ion irradiated MoS 2 originate from chalcogen vacancies 3 . The latter can be deterministically created with a precision below 10 nm 9 , underscoring the potential of defect engineering for twodimensional (quantum-) optoelectronics.…”
mentioning
confidence: 56%
“…ontrol over atomic defects is the foundation of today's semiconductor technology. For two-dimensional van der Waals semiconductors, the term "defect engineering" has been coined to suggest that, by introducing defects, these materials can be engineered beyond the established concepts of doping or alloying 1 , enabling advanced functionality, such as single photon sources 2,3 or photocatalysis with chemical specificity 1 . Nevertheless, the microscopic understanding of defect-related modifications remains elusive due to a lack of thorough correlation between atomic structure and resulting macroscopic electronic and optical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these defects are susceptible to ambient environments conditions [ 271 , 272 ]. Defects can also be created through the irradiations, metal doping and functionalization [ 273 , 274 ]. Thus, MoS 2 structures unavoidably have various defects in terms of vacancies, dopants, adsorbates, adatoms, and impurities.…”
Section: Mos 2 : a Unique Materials For Gas Sensingmentioning
confidence: 99%
“…[166] However, atomic defects can also be created on purpose in TMDCs, for example, by He ion irradiation which show single photon emission. [167,168] These rapid recent developments demonstrate that single photon emitters in TMDCs will establish a new class of artificial atoms in the solid state that can be interfaced with different kinds of strain sources. It has been shown that already excitons in plain mono-and bilayer TMDCs react to external strain tuning [169,170] and that even the exciton-phonon coupling can be controlled in this way.…”
Section: Artificial Atoms In Layered Materialsmentioning
confidence: 99%